The Influence of the Brainstorming Learning Model on Students' Learning Motivation in Pancasila Education Lessons in Grade VIII at SMP Pahlawan Nasional. - Tampubolon, Stevanie Febiola; Siregar, Hapni Laila (IJBLE Scientific Publications Community Inc., 2025)
Study This to study The Influence of Learning Models rainfall opinion (brainstorming ) to motivation Study students in the eye Pancasila Education lessons in class VIII.Research purposes this (1) For know motivation Study student on eye lesson Pancasila Education in class VIII(2) For know the influence of learning models rainfall opinion ( brainstorming ) for increase motivation Study students on eye lesson Pancasila Education in class VIII. Method research used in This Study is an experiment with a quasi-experimental design, specifically a nonequivalent control group design, involving two groups: class experiments and control classes. North Sumatra. With a population comprising all private junior high school students, national heroes, and research samples, this Study involves two classes. Technique data collection in research This is observation, questionnaires, and documentation. Then, the data obtained will be analyzed using descriptive analysis, Validity Tests, Reliability Tests, Normality Tests, Homogeneity Tests, and hypothesis tests with the SPSS 25 application. From the independent t-test, it is known that Sig. The value (2-tailed) is 0.000 or < 0.05. This means there is a significant mean difference in motivation between the group class control, conventional learning, and the class experiment using a learning model, as well as the opinion (Brainstorming) study. From the independent t-test, it is known that Sig. The value (2-tailed) is 0.000 or < 0.05. This means there is a significant difference in motivation between the group class control, conventional learning, and the class experiment using a learning model, as well as the opinion of rainfall (Brainstorming).